Safety and Efficacy of a Combination of Chloramphenicol, Polymyxin-B and Dexamethasone in Ocular Infection with Inflammation - Dilip Kiran, Dr. Mayuresh; Lalit Jeevan Pawaskar, Shaheen Naseem Sheikh, (International Journal of Innovative Research in Medical Science, 2018)
Introduction: Ocular infection with inflammation is very common in developing countries like India. Multi-drug therapy is used in the treatment of Ocular infection with inflammation. We studied the safety as well as efficacy of one such combination anti-bacterial (Chloramphenicol and Polymyxin -B) and corticosteroid (Dexamethasone) in the treatment of Ocular infection with inflammation especially mild keratitis and conjunctivitis. Methodology: Out of 151 patients, 117 were completed the study. Efficacy assessment was made by reduction in Visual Analogue Scale (VAS) Score of Ocular hypermia, Ocular discharge, Keratitis and Conjunctivitis related to Ocular infection with inflammation. Safety assessment was made by inspecting the adverse events during the study. Results: Reduction in mean VAS score was analysed from 4.47 (baseline) to 2.76 (day 3) to 0.55 (day 5) of ocular hypermia, from 3.42 (baseline) to 2.03 (day 3) to 0.24 (day 5) of ocular discharge, 3.57 (baseline) to 1.89 (day 3) to 0.21 (day 5) of keratitis and from 3.84 (baseline) to 2.10 (day 3) to 0.20 (day 5) of conjunctivitis. Majority of patients had more than 90% reduction in their VAS score at conclusion visit in all the parameters. 8.54% of adverse events of mild intensity was observed. Conclusion: A fixed dose combination of Chloramphenicol, Polymyxin-B and Dexamethasone of is safe and effective in the treatment of Ocular infection with inflammation.